2016
DOI: 10.1016/j.apjtm.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis in ulcerative colitis patients: Genetic diversity and analysis of laboratory findings

Abstract: The present study confirms previous findings that have indicated the predominance of Blastocystis ST3 in humans and contributes additional evidence that suggests the low colonisation of Blastocystis infection in ulcerative colitis patients during active stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In addition, Blastocystis colonization was significantly associated with high bacterial richness and Bacteroides enterotype and it was suggested that Blastocystis might be an indicator of a healthy intestinal flora rather than a dysbiosis (34,35). On the other hand, decreased Blastocystis colonization was reported in gastrointestinal disorders including inflammatory bowel diseases, ulcerative colitis, and irritable bowel syndrome (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Blastocystis colonization was significantly associated with high bacterial richness and Bacteroides enterotype and it was suggested that Blastocystis might be an indicator of a healthy intestinal flora rather than a dysbiosis (34,35). On the other hand, decreased Blastocystis colonization was reported in gastrointestinal disorders including inflammatory bowel diseases, ulcerative colitis, and irritable bowel syndrome (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the high sensitivity of real-time PCR tests has helped us understand that some parasites are-on an overall basis-much more common than previously anticipated, with prevalence rates approaching 100% in some communities, even in developed countries. Examples include Blastocystis and Dientamoeba, which appear to be more or less obligate eukaryotic members of the gut microbiota in some populations [15][16][17][18][19][20][21], while less frequent in others, including individuals with functional and organic bowel diseases and metabolic disorders [13,[22][23][24][25]. For instance, we recently showed Dientamoeba to be a consistent finding in the stool from children in childcare in Denmark [20], and similarly that Blastocystis is a frequent finding in children in Nigeria, with prevalence increasing by age [18].…”
mentioning
confidence: 96%
“…As B. hominis prevalence has been found to be greater in the healthy groups than in patients with UC in most studies, this suggests that B. hominis has a protective role rather than being a cause of UC and could be a marker of a healthy microbiota (23,30,32,33). In a healthy microbiota, the butyrate produced by bacteria is used for ATP production with β-oxidation by colon epithelial cells.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to these studies, Coşkun et al (30) examined B. hominis prevalence in the fecal cultures of 150 patients with UC and found it to be lower in active patients than in those in remission (active UC=3.8% vs. remission=11.8%, p<0.05).…”
Section: Discussionmentioning
confidence: 98%